Ícones no design de interfaces: user experience e acessibilidade digital - Melo, Erildo Vitor Medeiros (2019)
Throughout the history of mankind imagery representations have been used as a way of conveying messages, concepts and ideas. However, with the evolution of technologies, this language has gained more and more space and currently surrounds us routinely. This paper aims to discuss the function of icons in digital products, seeking to understand their effectiveness as a form of democratization of access to communication. For this, it was necessary to understand, beforehand, how the forms of representation called “icons” arose and how their use was being introduced and developed over time. Similarly, there was a need to explore the concepts of “user experience” and “accessibility”, topics strictly related to the inclusion and democratization of content for society. To achieve these objectives, a qualitative research was conducted through a questionnaire with structured script and applied via e-mail with six technology professionals, succeeded by an analysis of the information obtained with the answers. The research sought theoretical support from authors such as Kate Clair (2009), Cynthia Busic-Snyder (2009), Martine Joly (2012) and Donald A. Norman (2006), as the most important references. The conclusions of this study reveal that icons play a fundamental role in the democratization of information and the user-product relationship in the digital environment, since their use directly affects the user experience and accessibility in different spheres, being, nowadays, a crucial element in product interfaces that aim to win and build customer loyalty.